Dietary aflatoxin B1 induces abnormal deposition of melanin in the corium layer of the chicken shank possibly via promoting the expression of melanin synthesis-related genes - Yong-li WANG; Chao HUANG; Yang YU; Ri-chun CAI; Yong-chun SU; Zhi-wu CHEN; Mai-qing ZHENG; Huan-xian CUI (Journal of Integrative Agriculture, 2023)
San-Huang chicken is a high-quality breed in China with yellow feather, claw and break. However, the abnormal phenomenon of the yellow shank turning into green shank of San-Huang chicken has been a concern, as it seriously reduces the carcass quality and economic benefit of yellow-feathered broilers. In this study, the cause of this abnormal green skin in shank was systematically investigated. Physiological anatomy revealed that the abnormal skin in shank was primarily due to the deposition of melanin under the dermis. After analyzing multiple potential causes such as heredity (pedigree and genetic markers), environment (water quality monitoring) and feed composition (mycotoxin detection), excessive aflatoxin B1 (AFB1) in feed was screened, accompanied with a higher L-dihydroxy-phenylalanine (L-DOPA) (P<0.05) and melanin content (P<0.01). So it was speculated that excessive AFB1 might be the main cause of abnormal green skin in shank. Subsequently, the further results showed that a high concentration of AFB1 (>170 μg kg–1) indeed induced the abnormal green skin in shank compared to the normal AFB1 content (<10 μg kg–1), and the mRNA levels of TYR, TYRP1, MITE, MC1R and EDN3 genes related to melanin deposition would significantly up-regulate (P<0.01) and the content and activity of tyrosinase (TyR) significantly increased (P<0.05). At the same time, the content of L-DOPA and melanin deposition also increased significantly (P<0.01), which also confirmed the effect of excessive AFB1 on melanin deposition in skin of shank. Results of additional experiments revealed that the AFB1’s negative effect on melanin deposition in skin of shank could last for a longer time. Taken together, the results of this study explained the occurrence and possible mechanisms of the abnormal AFB1-related green skin in shank of chickens. Excessive AFB1 in diets increased the L-DOPA content and melanin abnormal deposition in the chicken shank possibly via promoting TyR content and activity, and the expression of melanin synthesis-related genes. Furthermore, our findings once again raised the alarm of the danger of AFB1 in the broiler production.